Determinan Kesejahteraan Masyarakat Kota Medan dan Tinjauannya dalam Perspektif Ekonomi Islam - Ferry Alqadri; Khairina Tambunan; Purnama Ramadani Silalahi (Journal of Economics and Management Scienties, 2026)
This study aims to identify and analyze the partial and simultaneous effects of Gross Regional Domestic Product (GRDP) per capita, the poverty rate, and the unemployment rate on community welfare, as measured by the Human Development Index (HDI), in Medan City. It also examines these determinants from the perspective of Islamic Economics. The study employed a quantitative approach with a causal associative research design. The data used were secondary time-series data covering the period from 2005 to 2025, obtained from Statistics Indonesia (Badan Pusat Statistik/BPS). The sampling technique applied was purposive sampling. To ensure an adequate sample size for macroeconomic statistical analysis, the annual data were transformed (disaggregated) into quarterly data, resulting in a total of 84 observational samples. The data were analyzed using multiple linear regression with SPSS version 26. The partial test (t-test) revealed that GRDP per capita has a positive and significant effect on community welfare (HDI). In contrast, the poverty rate and the unemployment rate were found to have negative and significant effects on the HDI of Medan City. Simultaneously (F-test), the three independent variables have a significant effect on the dependent variable, with a coefficient of determination (R²) of 80%, indicating that 80% of the variation in community welfare (HDI) is explained by the model, while the remaining 20% is influenced by other factors outside the scope of this study.